New understanding of factors influencing the seed germination of Jacaranda micrantha (CHAM.), an aesthetically appealing native species - Daniela Sanson; Alexandre Techy de Almeida Garrett; Fabiana Schmidt Bandeira Peres; Rogério Bobrowski (Revista Ceres)
ABSTRACT The factors and their levels influencing the seed germination process are well-known for most traditional forest species. But, for Jacaranda micrantha, a native and aesthetically appealing species, some factors influencing the germination process are not well described. So, we evaluated the effect of different light conditions and soaking on the germination of seeds. Four light intensity treatments (5, 25, 50, and 100%) and four soaking times were tested (0, 12, 24 and 48 hours). In both procedures, a completely randomized design was applied, with four treatments of four replicates containing 25 seeds each. Daily evaluations were performed to determine the germination percentage and the germination speed index (IVG). Seeds of J. micrantha presented a better germinative potential in lower light intensities, but more abnormal seedlings were observed at very low-intensity light (5%). The imbibition of seeds was efficient in accelerating the germination process, and the 12-hour soaking time in the water was the most efficient, contrary to what is described in the literature.